(untitled) (Dermatology Reports, 2023)
Macrophages respond against Mycobacterium leprae infection through interacting with vitamin D and vitamin D receptor (VDR). There has been no study analyzing the association between vitamin D and VDR with bacteriological index (BI) in leprosy patients in Indonesia. To analyze the serum level of 25- hydroxyvitamin D (25(OH)D) and plasma level of VDR as well as their association with BI in leprosy patients in Indonesia. This is a cross-sectional study. Serum level of 25(OH)D was assessed with in vitro chemiluminescent immunoassay. Plasma level of VDR was assessed with enzyme linked immunosorbent assay method. Median serum level of 25(OH)D was 12.68 ng/mL. There was no correlation between serum level of 25(OH)D and BI (r=0.033; p=0.869). Median plasma level of VDR was 1.36 ng/mL. There was no correlation between plasma level of VDR and BI (r=- 0.063; p=0.749) and no significant association between BI and serum level of 25(OH) and plasma level of VDR (R2=0.055). There was no association between serum level of 25(OH)D and plasma level of VDR with BI in leprosy patients.